The Human Capital Perspective in PT Jakarta International Container's CSR Program in Education through the Jala Samudra Mandiri Foundation. - Alwina Putriutami; Bambang Shergi Laksmono (Cita Konsultindo Research Center, 2024)
The implementation of Corporate Social Responsibility (CSR) embodies a company's duty to its surrounding environment, encompassing social issues. An illustration of this is the educational CSR collaboration between PT Jakarta International Container Terminal (JICT) and the Jala Samudera Mandiri Foundation. The purpose of this study is to outline the efforts to enhance human resources and to identify the key factors contributing to the sustainability of the cooperation between PT JICT and the Jala Samudera Mandiri Foundation through the CSR program Rumah Belajar JICT. Utilizing human capital theory as a tool, this study examines a series of policies and programs designed to promote skill and knowledge enhancement, thereby assisting individuals in advancing their ability to participate in the economy and attain an improved standard of living. This research is a qualitative descriptive study, with the analysis unit encompassing all parties involved in this CSR program, including the foundation's chairman, PT JICT, tutors, mentors, Rumah Belajar JICT students, and alumni. Informants were selected using purposive sampling. Data collection involved observation, document studies, and interviews. The findings of this study indicate that PT JICT's CSR implementation in the field of education through the Jala Samudera Mandiri Foundation has been highly effective, leading to the enhancement of the knowledge and skills of Rumah Belajar students. Furthermore, it has been determined that the targeted collaboration CSR strategy employed has been fitting and has resulted in a successful CSR program.